Kala-azar control program in Nepal: A program review from 1994-2006 - Bhandari, Gajananda Prakash (2008)
SUMMARY: The Visceral Leishmaniasis (VL) control program in Nepal started in 1993 including free diagnosis, treatment and indoor residual spraying. After 14 years the disease is far from being controlled. Elimination of VL in 2015 has recently been identified as a regional priority with high level of political commitment. We analyzed the VL control effort in Nepal over the period 19942006 and tried to formulate recommendations for the VL elimination initiative. This document of the VL control program in Nepal is based on literature review and on a case study. First, we reviewed articles on VL in Nepal published in medical journals through Pubmed, ISI Web of Science, Google scholar and by hand searching. Secondly, the grey literatures, mainly the reports on VL drafted by the Ministry of Health were reviewed for the period 1994-2006. The documents were obtained from key informants and from website of the Nepalese Ministry of Health. Thirdly, a case study is presented to analyze the performance of the VL elimination program in a "pilot district", where the program was launched in 2006. There are only few studies available on VL in Nepal discussing the epidemiology, diagnosis, treatment, vector bionomics, human behavior and prevention. The review of the grey literature from 1994-2006 revealed that the VL incidence rate remained almost constant since 1993 despite the control efforts. However, these are only the records of patients seeking health care at public health system. Moreover some indicators and especially the denominators of the indicators were changed during the period so interpretation of these data is difficult. The case study showed that there is a lack of trained human resources, laboratory facilities and treatment guidelines which is hindering the decentralization of VL elimination program. Strengthening of public health system by training of human resources, availability of appropriate diagnostic tests and treatment with guidelines at district level is necessary for better case management. Active case detection, intersectoral coordination, improved surveillance system can lead to success of VL control effort. Research should be encouraged to understand the disease and transmission, and to monitor control efforts.